NEWCASTLE DISEASE ANTIBODY TITER ON BROILER WITH VACCINATED AT DAY 1 AND GIVEN BOOSTER AT DAY 15 - Wisnantari, Ni Made Suksmadewi; Suardana, Ida Bagus Kade; Nindhia, Tjokorda Sari (Buletin Veteriner Udayana, 2022)
Newcastle Disease is one of the major infectious diseases that often attacks broiler farms. The objective of the study was to find out the number of Newcastle Disease antibody titers of broiler vaccinated at the age of a day in nursery and given booster in 15 days. The research sample was 20 broiler DOC divided into 2 groups and each group contained of 10 DOC. The control group (P0) was unvaccinated DOC of broiler and the group (P1) was vaccinated DOC of broiler at the age of a day in nursery and given booster in 15 days age. Blood samplings were conducted on the 7 th , 14 th , 21 st , and 28 th days in each group. Newcastle Disease antibody titer examination was done using Haemaglutination Inhibition. The antibody titer value was then analyzed using variance (Anova) and regression test. The results showed that booster vaccination performed at 15 days of age showed a protective antibody titer at 21 days of age, namely 5.8 HI log 2 (? 4 HI log 2) and increased up to 28 days of age, namely 6.5 HI log 2 (? 4 HI log 2). The conclusion of this study is that the Newcastle Disease broiler antibody titer increased after booster vaccination was performed at 15 days of age. Suggestions need to be given a booster vaccination in broilers vaccinated at day one.